Learning Philosophy at Pesantren: A Study of Pesantren Luhur Baitul Hikmah Malang - Muhammad Hilal (Journal of Contemporary Islamic Education, 2024)
The idea of a pesantren that accommodates philosophy in its curriculum seems to be a strange one still. The data in Direktorat Madrasah Diniyah dan Pondok Pesantren (The Directorate of Islamic Education and Pesantren) doesn't mention a kind of such pesantren whatsoever. The existence of Pesantren Luhur Baitul Hikmah changes that impression, so it is important to reveal the background of this pesantren and how philosophy is taught in it. To fulfill these goals, this research is designed to be qualitative that collects its data by observations, interviews and documentations and analyzes them by using Miles and Hubermann's technique. This research found that Pesantren Luhur Baitul Hikmah became so accommodative to philosophy because it was originally a discussion group that evolved to be a pesantren. Philosophy was taught there by using three methods inspired by Qur'anic verses 96:1-5. First, the bandongan teaching method through Arabic philosophical texts. Second, the discussion method comprises weekly discussion and accidental discussion. Third, the learning-through-writing method which has already become a cultural habit there due to the exemplary of the kiai, the proliferation of social media, and the more affordable printing costs.